1974
DOI: 10.1002/pssb.2220620112
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hyperfine Interaction and Structure in FeSiF6·6HO2 by Mössbauer Measurements

Abstract: Mossbauer, proton resonance, and susceptibility measurements (T 5 4.2 K) on FeSiF, .-6H,O can be understood with the hypothesis that there are three equivalent Fe(I1) sites related by C, operation and the effective symmetry of the ligand field at each Fe(I1) ion site is czh (or lower). The nonaxial susceptibility tensor x is related to the measured axial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
4

Year Published

1975
1975
1992
1992

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 17 publications
0
5
0
4
Order By: Relevance
“…[1,2]). Optical and crystallographic studies ( [3,4]) showed the occurrence of the phase transformation P3ml --+ P21/C in Fe, Mn, Mg-Fls at 230 K, 230 K, 300 K respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2]). Optical and crystallographic studies ( [3,4]) showed the occurrence of the phase transformation P3ml --+ P21/C in Fe, Mn, Mg-Fls at 230 K, 230 K, 300 K respectively.…”
mentioning
confidence: 99%
“…[1] and [2] respectively. The measured value of the average hyperfine field, agrees with the expectation value -9.7 kOe obtained from both crystal-field data.…”
mentioning
confidence: 99%
“…Des spectres de poudres soumises à des champs magnétiques ont aussi été publiés dans des études [8,9] d'inspirations diamétralement opposées : l'ajustement des spectres se fait, soit en fonction des caractéristiques d'un champ cristallin (non axial) agissant sur l'ion Fe2 +, et servant à calculer directement des spectres théoriques [8], soit en fonction de caractéristiques hyperfines associées à l'ion Fe2+ en site non axial, en utilisant alors un modèle phénoménologique pour synthétiser les spectres de poudres [9] ; ces dernières mesures se sont révélées en excellent accord avec les mesures faites sur monocristaux (étude [3]).…”
unclassified
“…At 4.3 I ( the asymmetry parameter 7 of the electric field gradient has been measured by several authors [ 3 to 51. The results vary between 0.15 [4] and 0.33 [5].…”
Section: Ho (Ffs) Ismentioning
confidence: 94%